Interdisciplinary practice on PET-SAÚDE for public school teachers - Kelly Alves de Almeida; Lara Teixeira Soares Nuto; Giselle Cavalcante de Oliveira; Flora Elizabeth Bellatrix de Pitombeira e Nogueira Holanda; Beliza Mara Rodrigues de Freitas; Magda Moura de Almeida (Universidade de Fortaleza, 2012)
Objectives: To explore the health status of public school teachers from the perspective of the physiotherapist and the speech pathologist, in order to develop and implement a proposal of preventive intervention for this population, through self-care measures carried out in groups. Methods: This is a research - action qualitative study, with the completion of six meetings that took place fortnightly, lasting 45 minutes in average, covering physical therapy and speech therapy self-care. At the first meeting, a questionnaire was applied to collect personal and professional data and variables: physical therapy, pain sites, seated posturepermanence, speech therapy, annoyance in their voice, throat exams, water intake, strategies to maintain the order in the classroom. The sample consisted on 12 teachers linked to a public elementary school in Fortaleza-CE, Brazil. Results: All teachers made complaintsabout pain in the body and the types of pain most frequently reported were burning and stabbing. The majority (83.3%) reported never been submitted to physical therapy to relieve symptoms. In respect to speech complaints, 91.6% (11) of the study group reported discomfortin his voice and only one has held speech therapy, for six months. Conclusions: Integral, intersectional and interdisciplinary actions are needed, in order to prevent and early detect and treat physical or speech disorders that are characteristic of the profession. Group work proved to be a rich in possibilities tool.